Dynamic changes in CD45RA−Foxp3high regulatory T-cells in chronic hepatitis C patients during antiviral therapy. (April 2016) - Li, Zhiqin; Ping, Yu; Yu, Zujiang; Wang, Meng; Yue, Dongli; Zhang, Zhen; Li, Jianbin; Zhang, Bin; Shi, Xuezhong; Zhang, Yi
Highlights: Activated regulatory T-cells (aTreg cells) were found to express high levels of CD39, CD73, and transforming growth factor beta (TGF-β). Total Treg cells and aTreg cells decreased during antiviral therapy. Targeting aTreg might be a future solution to prevent relapse of chronic hepatitis C. Summary: Objectives: CD4 + Foxp3 + regulatory T-cells (Treg) are known to accumulate under certain pathological conditions. This study was conducted to evaluate the characteristics of and dynamic changes in Treg cells in chronic hepatitis C (CHC) patients during antiviral therapy. Methods: One hundred and forty-five subjects were enrolled in this study, including 105 CHC patients and 40 healthy donors. The phenotypes and functions of Treg cells were analyzed by flow cytometry. Results: A significant elevation in Treg cells was observed in the peripheral blood of CHC patients compared with healthy donors. Interestingly, compared with non-suppressive Treg (non-Treg) and resting Treg (rTreg) cells, activated Treg (aTreg) cells expressed higher levels of ectonucleotidase, CD39, and CD73. After treatment with interferon alpha (IFN-α) and ribavirin (RBV) in vitro, the frequencies of total Treg cells and aTreg cells in peripheral blood mononuclear cells (PBMC), as well as the levels of transforming growth factor beta (TGF-β) secreted by aTreg and non-Treg cells, were significantly decreased. Importantly, it was found that levels of aTreg cells in patients with a sustained virological response (SVR) were lower than in relapsed patients, suggesting that a high frequency of aTreg cells might be associated with a poor clinical outcome in HCV infection. Conclusion: These results demonstrate a decreasing trend in aTreg cells, which express higher levels of CD39, CD73, and TGF-β, in SVR patients during antiviral therapy.